2020
DOI: 10.1186/s41256-020-00138-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among weight stigma, eating behaviors and stress in adolescents in Wuhan, China

Abstract: Background: The purpose of this study was to examine the relationships among weight stigma, eating behaviors, and stress, as well as to analyze the effect of stress in mediating the association between weight stigma and eating behaviors. Methods: The study involved 1818 adolescents between 14 to 19 years of age and was conducted in Wuhan, China in 2019. Weight stigma, eating behaviors (cognitive restraint, uncontrolled eating, and emotional eating), and stress were assessed by self-report questionnaires. Hiera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…This, in turn, was associated with higher UE which was ultimately associated with higher FA symptoms. These results are in line with a plethora of studies that put forward the pathways between NES and EE/UE (or between NES and eating-to-cope) as risk indicators for obesity (van Strien et al, 2016 ; Wang et al, 2020 ) or greater BMI (Boggiano et al, 2014 ; Burgess et al, 2014 ). These results suggest that, for some young adults, the consumption of palatable food is seen as an incentive to alleviate the distress associated with the critical life changes that characterize this developmental stage, a pattern that puts them at risk for developing altered eating behaviors, greater BMI, and obesity.…”
Section: Discussionsupporting
confidence: 85%
“…This, in turn, was associated with higher UE which was ultimately associated with higher FA symptoms. These results are in line with a plethora of studies that put forward the pathways between NES and EE/UE (or between NES and eating-to-cope) as risk indicators for obesity (van Strien et al, 2016 ; Wang et al, 2020 ) or greater BMI (Boggiano et al, 2014 ; Burgess et al, 2014 ). These results suggest that, for some young adults, the consumption of palatable food is seen as an incentive to alleviate the distress associated with the critical life changes that characterize this developmental stage, a pattern that puts them at risk for developing altered eating behaviors, greater BMI, and obesity.…”
Section: Discussionsupporting
confidence: 85%
“…Consistent with a previous study [ 4 ], our study demonstrated a correlation between PWS and eating disturbances in low weight participants. Individuals with low weight could experience perceived pressure to be thin, which may be associated with body dissatisfaction or eating disturbances (i.e., cognitive restraint) [ 36 ]. Social and cultural pressure to achieve the thin ideal and fit ideal is associated with eating disturbances in young adults [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…This research underpins cross-sectional evidence supporting an expanded tripartite influence model of ED risk whereby family, peer, partner, and media pressures about weight are associated with disordered eating through the internalization of the thin ideal, and over a decade of studies showing that internalized and experienced weight stigma are related to disordered eating (39–43).…”
Section: Introductionmentioning
confidence: 70%